Statistical characteristics of some Indian hydrologic time series (MAUSAM, 1980)
Extensive literature exists on the analysis and construction of models of stream-flows in the temperate regions, whereas the hydrology of tropical monsoon affected rivers have not received much attention. An analysis of the monthly and annual rainfall and runoff data from the Krishna and Godavari river basins in India and the Wabash river basin in the United States are presented in this paper. The Krishna and Godavari rivers are in the tropical, monsoon region whereas the Wabash river is in the temperate zone. The basic statistics, and the spectral analysis of the data are presented and compared. The implications of the data structure to modeling these flow sequences are discussed.